2016
DOI: 10.1021/acs.est.5b05101
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Photochemical Conversion of NO2 to HONO on the Humic Acid Surface under Simulated Sunlight

Abstract: The poor understanding of HONO sources in the daytime highlights the importance of the heterogeneous photochemical reaction of NO2 with aerosol or soil surfaces. The conversion of NO2 to HONO on humic acid (HA) under simulated sunlight was investigated using a flow tube reactor at ambient pressure. The uptake coefficient (γ) of NO2 linearly increased with irradiation intensity and HA mass in the range of 0-2.0 μg/cm(2), while it decreased with the NO2 concentration. The HONO yield was found to be independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
114
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 54 publications
15
114
4
1
Order By: Relevance
“…The calculated k eff values and uptake coefficient are in the same range and match the NO 2 uptake coefficients on irradiated humic acid surfaces (coatings) and aerosols obtained by Stemmler et al (2006/07) which were in between 2×10 −6 and 2×10 −5 (coatings) and 1×10 −6 and 6×10 −6 (aerosols), depending on NO 2 concentrations and light intensities. Similar NO 2 uptake coefficients on humic acid were observed by Han et al (2016). George et al (2005) reported about a 2-fold increased NO 2 uptake coefficients for irradiated organic substrates (benzophenone, catechol, anthracene) compared to dark conditions, in the order of (0.6-5) × 10 −6 .…”
Section: Kinetic Studiessupporting
confidence: 72%
See 2 more Smart Citations
“…The calculated k eff values and uptake coefficient are in the same range and match the NO 2 uptake coefficients on irradiated humic acid surfaces (coatings) and aerosols obtained by Stemmler et al (2006/07) which were in between 2×10 −6 and 2×10 −5 (coatings) and 1×10 −6 and 6×10 −6 (aerosols), depending on NO 2 concentrations and light intensities. Similar NO 2 uptake coefficients on humic acid were observed by Han et al (2016). George et al (2005) reported about a 2-fold increased NO 2 uptake coefficients for irradiated organic substrates (benzophenone, catechol, anthracene) compared to dark conditions, in the order of (0.6-5) × 10 −6 .…”
Section: Kinetic Studiessupporting
confidence: 72%
“…Accordingly, NO 2 uptake on glass is assumed to be significantly lower than on proteins. A strong increase in NO 2 uptake coefficients with increasing coating thickness was also observed for humic acid coatings (Han et al, 2016). However, they found an upper threshold value of 2 µg cm −2 of cover load (20 nm absolute thickness, assuming a humic acid density of 1 g cm −3 ), above which uptake coefficients were found to be constant.…”
Section: Impact Of Coating Thicknessmentioning
confidence: 90%
See 1 more Smart Citation
“…These results stimulated laboratory investigations on potential HONO precursors from which the most frequently discussed mechanisms are (i) the photosensitized reduction of nitrogen dioxide (NO 2 ) by organic material, e.g. humic acids (George et al, 2005;Stemmler et al, 2006;2007, Sosedova et al, 2011Han et al, 2016), (ii) the photolysis of adsorbed nitric acid (Zhou et al, , 2011Laufs and Kleffmann, 2016), (iii) biogenic production of nitrite in soil (Su et al, 2011;Ostwald et al, 2013;Maljanen et al, 2013;Oswald et al, 2015;Scharko et al, 2015;Weber, 2015) and (iv) release of adsorbed HONO from soil surfaces after deposition of strong acids (VandenBoer et al, 2013(VandenBoer et al, , 2014(VandenBoer et al, , 2015Donaldson et al, 2014). Another discussed source, the reaction of excited gaseous NO 2 with water (Li et al, 2008), is of minor importance as demonstrated by laboratory (Crowley and Carl, 1997;Carr et al, 2009;Amedro et al, 2011) and modelling studies (Sörgel et al, 2011b;Czader et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…humic acid, minerals, proteins and organically coated particles (Ammann et al, 1998;Arens et al, 2001;Aubin et al, 2007;Bröske et al, 2003;Han et al, 2016;Kalberer et al, 1999;Kleffmann et al, 1999;Kleffmann and Wiesen, 2005;Lelièvre et al, 2004;Kinugawa et al, 2011;Liu et al, 2015;Wang et al, 2003;Yabushita et al, 2009;Meusel et al, 2017). Light can activate some of these surfaces (humic acid, proteins and other organic compounds, titanium dioxide, soot), which enhances NO 2 uptake and HONO production (George et al, 2005;Langridge et al, 2009;Monge et al, 2010;Ndour et al, 2008;Ramazan et al, 2004;Stemmler et al, 2007;Kebede et al, 2013;Meusel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%